Impact of Birth Weight and Vitamin D Levels on Anthropometric Measurements of Infants in Benghazi, Libya: A Cross-Sectional Study - Elfagi, Salima; Faiza Nouh; Mohammed Buzgeia; Amina Aljegdaf; Amina Atalhe; Aya Aljihany; Fatima Ariedh (AlQalam Journal of Medical and Applied Sciences, 2025)
Birth weight significantly influences infant health, affecting vulnerability to illnesses and survival chances. Infants weighing <2.5 kg are at a higher lifelong risk of health problems. Vitamin D, a vital nutrient, plays an essential role in infant growth and development. This study aimed to examine the effect of birth weight and vitamin D status on anthropometric measurements of infants under one year. A cross-sectional study was conducted from November 2023 to June 2024 on 434 healthy infants born in public and private hospitals in Benghazi. Data collection occurred between December 2023 and March 2024 using a structured questionnaire covering socioeconomic data, anthropometrics, knowledge-attitude-practice (KAP), and infant behavior. The sample included 50.7% females and 49.3% males. Mean birth weight was 2935.83 ± 725.60 g. Normal birth weight (2500–<4000 g) was observed in 55.3% of infants born to mothers aged 18–35 years and 46.5% delivered via Caesarean section. Present weight correlated significantly with length (r=0.762, p<0.001), head circumference (r=0.720, p<0.001), and chest circumference (r=0.608, p<0.001). Vitamin D level showed strong associations with crawling onset, teething (p<0.001), and sleep quality (p=0.008), as well as infant age, maternal education, and family income. Gender correlated with vitamin D, birth weight, and wasting (p<0.05). Birth weight was strongly associated with BMI (r=0.824), wasting (r=0.850), and stunting (r=-0.766) (all p<0.001). Birth weight and vitamin D status significantly influence infant growth indicators and developmental milestones, highlighting their critical role in early health outcomes.